2000
DOI: 10.1083/jcb.149.6.1249
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Kinase Pyk-2/Raftk Regulates Natural Killer (Nk) Cell Cytotoxic Response, and Is Translocated and Activated upon Specific Target Cell Recognition and Killing

Abstract: The compartmentalization of plasma membrane proteins has a key role in regulation of lymphocyte activation and development of immunity. We found that the proline-rich tyrosine kinase-2 (PYK-2/RAFTK) colocalized with the microtubule-organizing center (MTOC) at the trailing edge of migrating natural killer (NK) cells. When polyclonal NK cells bound to K562 targets, PYK-2 translocated to the area of NK–target cell interaction. The specificity of this process was assessed with NK cell clones bearing activatory or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
74
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 74 publications
(85 reference statements)
15
74
0
Order By: Relevance
“…The overexpression of GFP-Pyk2-WT or GFP-Pyk2-K457A reduced the ability of NK-92 cells to lyse K562 target cells (Fig. 7B), consistent with a previous report demonstrating that overexpression of WT Pyk2 and kinase-inactive mutant Pyk2 blocked the cytotoxic response of NK cells (35). However, GFP-Pyk2-Y402F overexpression did not inhibit NK cytolytic activity (Fig.…”
Section: Il-15-induced Socs2 Stimulates the Degradation Of Phosphorylsupporting
confidence: 92%
“…The overexpression of GFP-Pyk2-WT or GFP-Pyk2-K457A reduced the ability of NK-92 cells to lyse K562 target cells (Fig. 7B), consistent with a previous report demonstrating that overexpression of WT Pyk2 and kinase-inactive mutant Pyk2 blocked the cytotoxic response of NK cells (35). However, GFP-Pyk2-Y402F overexpression did not inhibit NK cytolytic activity (Fig.…”
Section: Il-15-induced Socs2 Stimulates the Degradation Of Phosphorylsupporting
confidence: 92%
“…As controls, the signaling molecule PYK-2, as well as the MTOC and talin (data not shown), were also localized at NK cell-target cell contact areas, as reported for activated NK cells ( Fig. 2A, see arrowheads) (28). LAT was homogeneously distributed on the plasma membrane, but a patch was observed at the central zone of NK cell-target cell contact, colocalizing with the 2B4 cluster ( Fig.…”
Section: The 2b4 and Sap Localized At The Contact Area Of Resting Nk supporting
confidence: 74%
“…3, rows 1, 2, 5, 6, and 7) suggest that these signaling molecules might be translocated along with MTOC to the contact area with target cells during initiation of the cytolytic signaling cascade. The recent finding of PYK-2 association and cotranslocation with MTOC in cytolytic NK effector function supports this model for temporal and spatial regulation of cytotoxicity (28).…”
Section: Discussionsupporting
confidence: 52%
“…It has been shown that lipid rafts, enriched in signaling molecules, become polarized to the cell-cell contact area in NK cell conjugates with sensitive tumor cells, and this redistribution requires activation of Src and Syk kinases (27). It has also been shown that translocation of the MTOC is associated with activation of the tyrosine kinase, PYK-2 (28). In two other recent reports the inhibitory NK receptors and their corresponding MHC class I ligands were shown to colocalize in the contact area between NK cells and target cells (29,30).…”
mentioning
confidence: 99%